1978
DOI: 10.1172/jci109018
|View full text |Cite
|
Sign up to set email alerts
|

Attachment role of gonococcal pili. Optimum conditions and quantitation of adherence of isolated pili to human cells in vitro.

Abstract: A B S T R A C T Gonococcal pili facilitate attachment of virulent Neisseria gonorrhoeae to human cells. To characterize this attachment function, purified gonococcal pili isolated from four strains possessing antigenically distinct pili were radiolabeled with 125I and used to measure the attachment of pili to various human cells in vitro. Human buccal and cervical-vaginal mucosal epithelial cells, fallopian tube mucosa, and sperm bound pili in greater numbers per ,um2 of surface area (1-10) than fetal tonsil f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
35
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…In gram-negative pathogens, fimbriae are surface organelles which mediate host cell binding (21) and are important virulence factors in uropathogenic strains of E. coli, Proteus mirabilis, Salmonella, Serratia, Neisseria, etc. (15,29,38,43).…”
mentioning
confidence: 99%
“…In gram-negative pathogens, fimbriae are surface organelles which mediate host cell binding (21) and are important virulence factors in uropathogenic strains of E. coli, Proteus mirabilis, Salmonella, Serratia, Neisseria, etc. (15,29,38,43).…”
mentioning
confidence: 99%
“…One of these is the enzyme prepilin peptidase, which cleaves and then N methylates the precursor pilin subunits prior to their assembly into pili. We have used a PCR amplification strategy to clone the N. Pili are important virulence factors for certain types of human bacterial pathogens, such as Pseudomonas aeruginosa (9, 67), Vibrio cholerae (64), and Neisseria gonorrhoeae (43, 61). These three species all produce type IV pili composed of a single major protein subunit (pilin).…”
mentioning
confidence: 99%
“…Pili are important virulence factors for certain types of human bacterial pathogens, such as Pseudomonas aeruginosa (9,67), Vibrio cholerae (64), and Neisseria gonorrhoeae (43,61). These three species all produce type IV pili composed of a single major protein subunit (pilin).…”
mentioning
confidence: 99%
“…(19) have demonstrated an intriguing correlation among the properties ofhemolysin production, human erythrocyte agglutination, and virulence for chick embryos in E. coli isolated from extraintestinal infections in humans. Adherence to epithelial cells is a critical requirement for virulence of a number of bacteria, including Enterobacteriaceae (20)(21)(22), gonococci (23,24), and streptococci (25). Alternatively, other investigators have suggested that bacterial adherence may in some circumstances subserve host defenses by the elimination of attached bacteria on sloughing epithelial cells (26,27).…”
Section: Discussionmentioning
confidence: 99%